Kinematic Analysis of the Lower Limb in Uchi-Mata: Comparison Between Elite Athletes Specializing and Non-Specializing - Aedo-Munoz, E; Brito, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Uchi-mata is one of the most frequently used throwing techniques in judo, yet little is known about the kinematic factors distinguishing specialists from non-specialists. This study compared lower-limb kinematics during uchi-mata across its three phases in elite judokas. Methods: Forty athletes (12 female, 28 male; 24.5 ± 5.9 years) were classified as specialists (n = 20) or non-specialists (n = 20). Photogrammetry assessed hip, knee, and foot displacement, velocity, acceleration, and timing during the Approach, Turning, and Throw phases. Analyses were performed using mixed-effects models with group, phase, and sex as fixed effects, plus exploratory multivariate tests (p < 0.05). Results: Specialists executed faster movements in the Approach (p = 0.036, d = 0.69) and Throw phases (p = 0.010, d = 0.85), showed greater hip displacement during Approach (p = 0.008, d = 0.89), and achieved superior knee and foot displacement in Throw (p = 0.005 and p = 0.003). Final positioning also differed, with specialists displaying higher knee (98.5 ± 14.5 vs. 86.3 ± 17.8 cm, p ≤ 0.001) and foot (121.0 ± 19.7 vs. 104.4 ± 27.4 cm, p = 0.034) heights, but lower hip position (61.9 ± 4.2 vs. 75.6 ± 7.5 cm, p = 0.021). Sex showed no significant effects or interactions, indicating that these group differences were consistent across male and female athletes. Conclusions: Uchi-mata specialists demonstrated superior displacement and velocity control, particularly in the Approach and Throw phases, reflecting greater neuromuscular coordination and efficiency. These findings provide practical markers for coaches and athletes to guide training focused on mobility, strength, and technical drills that enhance hip, knee, and foot displacement, supporting the optimization of uchi-mata performance in elite judo. © 2025 by the authors.